ANALYSIS OF BRAKING SYSTEM ON ENERGY SAVING CARS "SAKERA", MECHANICAL ENGINEERING WORK, UM SURABAYA - Saifullo, Saifullo; Batutah, Moh Arif; Rizaly, Anastas; Ponidi, Ponidi; Kusnanto, Hadi; Sofana, Ilyas (International Journal of Mechanical Engineering Technologies and Applications, 2024)
A braking system in a vehicle has a very important role in maintaining the safety of drivers and passengers, and preventing accidents. The brake system functions to reduce speed (slow down) and stop the vehicle. A good braking system provides safety and comfort for the drivers. Therefore, it is necessary to design the right braking system for “Sakera” car. In this study, an analysis and calculation of the braking system was carried out to determine the required braking force at a speed of 50 km/hour and other speeds in a distance of 15 m. The data taken in this study was the specification of the braking system used in the Sakera car. The braking system analysis was carried out on flat roads with varying speeds, namely 30 km/h, 35 km/h, 40 km/h, 45 km/h, and 50 km/h with a distance of 15 m for braking. The conclusions of the analysis were obtained, namely the greater the speed of Sakera's car, the greater the braking force to stop the car, the hydraulic pressure on the hose, and the force of the driver's feet, as well as the braking force needed on road conditions with a slope angle of 20º, which is 839.362 N.